Y=-6x+8

You have to know what Y is to solve for X, or what X is to solve for Y.

If Y is zero, for example, then you think

0 = 6x+12.

Ask yourself what plus 12 would equal 0. Negative 12, right?

So

0 = (-12)+12

6x = (-12)

x = (-2) (because -2 times 6 = -12)

So, you might have an answer like

If Y= 0, then X = -2

But that's assuming Y is 0, and there's no reason to assume that. If Y is some other number, then X will also be a different number!

If Y is 36, say, then you have

36 = 6x+12

What plus 12 makes 36? 24. Therefore

6x = 24 so

x = 4 (because 6 x 4 is 24)

So

If Y = 36, then X = 4.

If Y is zero, for example, then you think

0 = 6x+12.

Ask yourself what plus 12 would equal 0. Negative 12, right?

So

0 = (-12)+12

6x = (-12)

x = (-2) (because -2 times 6 = -12)

So, you might have an answer like

If Y= 0, then X = -2

But that's assuming Y is 0, and there's no reason to assume that. If Y is some other number, then X will also be a different number!

If Y is 36, say, then you have

36 = 6x+12

What plus 12 makes 36? 24. Therefore

6x = 24 so

x = 4 (because 6 x 4 is 24)

So

If Y = 36, then X = 4.